Pengembangan Aplikasi Mobile Pencatat Hasil Lomba Tembak Reaksi menggunakan Stop plate Sensor Getar berbasis Arduino - Rakha Hasan Pramudito; Herman Tolle; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The task carried out by a Range officer in overseeing the course of a practical shooting match is quite a lot. From supervising participants, recording the results of the stage execution, handling damage to stage equipment if there is damage during the competition. In addition, the longer a competition lasts, the greater the possibility of errors in recording the results of the stage results. This can happen because of lack of energy, weather conditions, location of the match, and so on. To reduce the task load of the range officer, a recording application is needed to assist the range officer in recording the results of each stage carried out by each participant, as well as conducting data collection and recapitulation of the results of the competition, and directly upload data to the database. The recording system for a practical shooting match was developed using a combination of three technologies, namely an android smartphone, an arduino microcontroller, and a structured database. Smartphones are used as a tool to manage competition data and enter values into the database, microcontrollers are used to make stop plates that are used at the match stage, and databases are used for storing match data. In the android application implemented using the Kotlin programming language, the database is implemented using MySQL. After conducting black box testing to ensure the implementation of functional requirements has functioned as required, it was found that all the needs have been successfully implemented. Hit factor calculation test is done by comparing the calculation of the range officer helper application with the WinMSS program. The results of these tests get the difference calculation does not produce a significant difference that can affect the results of the match